ANALISIS KESULITAN SISWA MTsN KECAMATAN RANAH PESISIR TERHADAP SOAL PROBLEM SOLVING MATHEMATIC - Okviani Syafti (STKIP Pesisir Selatan, 2018)
This study aims to describe students’ difficulties in solving the problem solving mathematic problem and its causal factors. This research is qualitative descriptive research. The subject of this research is the students of class VII MTsN 12 Pesisir Selatan located in Ranah Pesisir subdistrict with the sample chosen by purposive sampling. Data obtained through tests, interviews and observations. Data validated by triangulation method. The data analysis framework is reviewed from the problem solving steps of understanding problem, problem solving strategy and problem solving result and interpretation of problem solving result (conclusion). Data analysis techniques used in this study is the percentage and data analysis techniques according to Milles and Hubermen for the analysis of difficulty and factors causing the difficulty.The results of data analysis show that, first difficulties experienced by students in understanding the problem that is identifying what is known and asked and make problems in symbol or mathematical model. Second, the students have difficulties in making the settlement strategy because they can not relate the concept to the problem or the ability of the students' mathematical connection is still weak. Third, students have difficulty in calculating the settlement because of difficulties in understanding the concept. Fourth, students who have difficulty in the previous step also have difficulty in interpreting the answers correctly